(untitled) (Research, Society and Development, 2021)
Objective: The objective of the study was to estimate and analyze the Potential Renal Acid Load (PRAL) of the diet in patients maintenance hemodialysis who are candidates for transplantation. Methodology: A cross-sectional study was conducted. The sample was separated in terciles of the PRAL. For the association between the PRAL and the independent variables, non-adjusted multinomial logistic regression and adjusted by potential confounders were implemented. It was assumed a p< 0,05 for statistical significance. Results: It was noticed that protein (g), the protein /kg of weight (g/kg), % of animal and vegetal protein, the phosphorus (mg), the lipid (g), and the carbohydrate (g) showed differences between the terciles (p<0,05). In regression, the greatest consumption of protein (g), protein g/kg of weight (g/kg), % of animal protein and lipid (g) was associated with the tercile 3 to tercile 1, whereas the greatest consumption of carbohydrate and % vegetal protein showed a protective effect. Conclusion: The results show an association between the PRAL and the protein consumption with the difference between the sources. It was not found an association between PRAL and the variables of nutritional status.